The French commercial code in English, 2007 (Oxford University Press, 2008)
The new 2007 edition incorporates changes to five of the eight Books of the Code - Books I, II, III, VI, and VII. The majority of the changes appear in Book II in the sections relating to the management and administration of public limited companies, as well as the many changes made to the sections relating to share capital and the shareholdings of employees. Also addressed in this edition are amendments to sections relating to commercial transactions, commercial persons, public auction sales, undertakings in difficulty and the registry of the Commercial Court